2017
DOI: 10.1016/j.molcel.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

A [Cu]rious Ribosomal Profiling Pattern Leads to the Discovery of Ribosomal Frameshifting in the Synthesis of a Copper Chaperone

Abstract: In many bacteria, separate genes encode a copper binding chaperone and a copper efflux pump, but in some the chaperone encoding gene has been elusive. In this issue of Molecular Cell, Meydan et al. (2017) report that ribosomes translating the ORF that encodes the copper pump frequently frameshift and terminate to produce the copper chaperone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…reported the discovery and functional characterization of efficient ribosomal frameshifting in the Escherichia coli ( E. coli ) copA gene ( Meydan et al., 2017 ). This finding is well supported by external ribosome profiling data that prompted their investigation ( Li et al., 2014 ; Atkins et al., 2017 ) and was subsequently confirmed by an independent study ( Drees et al., 2017 ). Along with this important discovery, the authors reported that ribosomal frameshifting occurs in the APT7B gene, which is a human ortholog of copA .…”
Section: Introductionsupporting
confidence: 67%
“…reported the discovery and functional characterization of efficient ribosomal frameshifting in the Escherichia coli ( E. coli ) copA gene ( Meydan et al., 2017 ). This finding is well supported by external ribosome profiling data that prompted their investigation ( Li et al., 2014 ; Atkins et al., 2017 ) and was subsequently confirmed by an independent study ( Drees et al., 2017 ). Along with this important discovery, the authors reported that ribosomal frameshifting occurs in the APT7B gene, which is a human ortholog of copA .…”
Section: Introductionsupporting
confidence: 67%
“…One type of recoding and splicing are alternatively used in different occurrences of one set of othologs ( 74 76 ), in several instances one type of recoding has been replaced by a different type ( 16 ). One example of the latter is dnaX where in E. coli expression of a second protein product involves a ribosomal frameshift event and in other bacteria including Thermus thermophilus , synthesis of the counterpart product involves transcription slippage ( 20 , 77 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another translation pattern is stop-codon read-through which we have described in the nervous system (Figure 3; von der Haar and Tuite, 2007;Jungreis et al, 2016;Li and Zhang, 2019). Ribosome profiling can also analyze frameshift mutations in the main open reading frame, although it has not been remarkably successful (Atkins et al, 2017).…”
Section: Applications Of Translatomics In Other Fieldsmentioning
confidence: 99%